Trajetória acadêmica e empregabilidade dos egressos do curso de Administração: um estudo a partir da Teoria do Capital Humano - Murad, Isabela (2017)
This study was carried out with the objective of understanding the academic trajectory of the graduates of the Administration course through Human Capital Theory. Specifically, we sought to know and analyze the academic trajectory of the graduates, as well as their relationship with employability. Faced with the discussion about higher education in Administration, in which several authors point to a training focused exclusively on employability, it is pertinent to research this scenario. This research is based on the Human Capital Theory, proposed by Schultz (1960), and is the basis for understanding part of this academic trajectory. The performance of this research is justified by social, personal and academic-scientific questions, represented by the relevance of the Administration course, by the personal and professional trajectory of the researcher, and by having graduates as subjects of research who have already experienced the entire training process . A qualitative study was done, collecting the data through semi-structured interviews, which covered three stages of the students' academic trajectory: before entering the Administration course, during and after the course. The thematic content analysis technique was used to analyze the data, being presented in three categories. The results can be understood from the TCH considering the assumptions of the constant search for qualifications and improvement of the curriculum; Investment in human capital through education; Focus on employability; Social mobility and the individual responsibility to invest in them. The investment in human capital was observed in schooling, experience, social mobility and in the post-school. It was noted that the logic of TCH is already present in high school, with a focus on employability. However, it was also possible to observe in the narratives a broader notion of the role of higher education, involving the critical sense, the citizen formation and the questioning of reali ty. During the university the interviewees experienced various experiences through extracurricular activities, disciplines and other training instances, which exceeded the notion of preparation for the exercise of the profession, enabling professional and personal development. Although employability has been highlighted by the interviewees at various times, it is possible to conclude that higher education has a meaning that goes beyond the initial idea of simply getting a good job when graduating. Thus, not only the development of technical skills, but also of interpersonal skills and attitudes involving citizenship and critical reflection, as well as the change in thinking and analyzing situations. It was possible to know another part of the trajectory of the graduates, who departed a little from TCH's propositions. This study contributes to bring a more optimistic view about higher education in Administration, because there are discussions that point to the predominance of technical education, guided by t he logic of TCH. It is clear that at the end of the trajectory the graduates attribute importance to higher education that transcends the preparation for the professional performance. For them, the stage in the university acquires varied meanings that involve transformation, evolution, professional development and mainly personal, reflected in the numerous experiences lived during this period.